MAX-phase Ti2AlC ceramics: syntheses, properties and feasibility of applications in micro electrical discharge machining - 정국현; 백경래; Teng Fei Zhang; 김광호; 김규정; 신현일; 강명창 (Journal of ceramic processing research, 2016)
MAX-phase Ti2AlC bulk ceramic was rapidly fabricated by spark plasma sintering (SPS) at 1000 oC and 1100 oC. To obtainmonolithic MAX-phase Ti2AlC, the molar composition (Ti:Al:C) was varied from 1:0.9:1 to 1:1.4:1. The microstructure andmaterial properties of the Ti2AlC ceramics were systematically investigated. The results show an optimized Al mole fractionof 1.1, with which nearly pure MAX-phase Ti2AlC ceramics were synthesized. Insufficient or excessive Al content resulted inimpurities. The maximum relative density, hardness, electrical and thermal conductivities were also obtained at an Al molefraction of 1.1. These properties were superior to those of Ti-6Al-4V alloys. The micro-Electrical Discharge Machining(ì-EDM)results showed that the MAX-phase Ti2AlC ceramics exhibited smaller average micro-hole diameters, shorter machining times,and shorter electrode wear lengths after machining than commercial Ti-6Al-4V alloys, with no obvious local erosion damagenear the hole entrance and no tapering effect inside the microholes. This should be attributed to the excellent electrical andthermal characteristics of MAX phases. This demonstrates that MAX-phase Ti2AlC ceramics are promising candidate for inmicro-EDM applications. KCI Citation Count: 5